The impact of hexagon drill on the agility of junior men's tennis players - Pratama, Rivan Saghita; Santosa, Teguh; Lengkana, Anggi Setia; Imron, Fatkhul; Mahardika, Wisnu; Hidayah, Taufiq (Universitas Negeri Yogyakarta, 2023)
The modern tennis games is characterized by an emphasis on quickness and strength. Rapid and multidirectional changes in the ball's speed necessitate a high level of agility. This study aimed to determine the impact of hexagon drill training on the agility of male junior tennis players. This research is a quantitative type with experimental methods. The research design uses a one group pre-test and post-test design. The population in this study were junior male tennis players in Jawa Tengah with the sampling technique using purposive sampling. The characteristics of the sample determined by the researcher were male, athletes under 18 years of age, and practicing in the Jawa Tengah area. The number of samples used in the study was 40 people. Data analysis used the t-test by first carrying out the normality test and homogeneity test. The results of the data normality test in this study were 0.06 > 0.05 (0.06 greater than 0.05), which means that the data is normally distributed in the population frequency. The results of the homogeneity test in this study were 0.15 > 0.05 (0.15 greater than 0.05), which means the data is homogeneous. After the data is normally distributed and homogeneous, the researcher continues data processing, namely the t-test. The results of the t-test showed a significance value of 0.000 so it was less than 0.05 or 0.000 <0.05 so there was a significant effect. The conclusion is that the hexagon drill exercise has an effect on increasing agility in junior men's tennis players in Central Java. Suggestions from researchers are that coaches can apply hexagon drill exercises to train junior tennis players under the age of 18 years.